Heaven on Earth: A Biblical Model for Parenting - Sandberg, Lynn
God is the perfect father, and you can improve your parenting style by looking to Him. He sets the example for how to be a provider, protector, teacher, and disciplinarian. This guidebook to Christian parenting explores the attributes of God a parent should try to emulate. It also brings to light four ways that Jesus grew in Luke 2:52, developing intellectually, physically, spiritually, and socially. As a parent, you can help your children follow in their savior’s footsteps. Just as the Lord disciplines those He loves, parents must discipline their children. Heaven on Earth carefully describes biblical principles to help parents provide the environment children need. It offers proper and healthy techniques to aid parents in leading children to honor and respect not only their parents but ultimately the Lord. What’s more, it draws a line between appropriate and abusive actions to control children’s behavior. Parents can proactively develop a disciplinary plan to guard against crossing these boundaries. Parents face many challenges to lead and guide the family in godly ways, and many struggle with the feelings of anger and failure. Find encouragement and strength through the power of God’s Word and the strength of the Holy Spirit, and get practical help in facing rebellious and wayward children. You can be inspired to overcome any obstacle, and raise your children for the glory of God.